Les dommages épistémiques en recherche : rétablir la confiance des personnes trans envers les chercheur·euse·s en position de privilège en travail social à travers la pratique de la responsabilité épistémique - Marie-Claire Gauthier (Éducation et Socialisation)
This article focuses on the power dynamics between social work researchers in positions of privilege and marginalized groups. It suggests that epistemic injustices experienced by certain marginalized groups cause epistemic damage, including loss of trust in: 1) knowledge-producing institutions; 2) researchers; and 3) the groups themselves and their capacity to produce legitimate knowledge. Using the notion of epistemic injustice and epistemic damage and analyzing the specific case of trans people in social work, the article aims to answer the following question: what attitudes can researchers adopt to avoid epistemic damage and to restore the trust of marginalized groups in themselves and in research? From this perspective, the practice of epistemic accountability appears to be essential to rebuilding this trust.